Rekonsiliasi Konflik Ambon Berbasis Nilai–Nilai Kearifan Lokal Pela Gandong, 1999-2002 - Hidayat Hasan; Sulasman (Tsaqofah, 2022)
Pela gandong is a local wisdom that was born from the social dynamics of the people of Central Maluku. The values ​​contained in pela gandong became the initial capital for social reconciliation of the fractured relationship after the 1999-2002 conflict. This study tries to answer three main problems, namely: first, how did the conflict occur and what caused it. Second, what is the impact arising from the 1999-2002 conflict events and third, what is the role of pela gandong values ​​as a media for resolution after the 1999-2002 conflict. This research is a literature study (library research). This type of research is a qualitative research using a historical approach. The findings of this study prove that Pela Gandong as a medium for conflict resolution is more effective for the social historical reconstruction of Salam-Sarane, which is based on the integration of the value system contained in Pela Gandong, namely; brotherhood between countries, solidarity, harmony, and religiosity. These values ​​become the basis for maintaining the integrity of inter-religious life in Ambon.